The Links of Ghrelin to Incretins, Insulin, Glucagon, and Leptin After Bariatric Surgery - Skuratovskaia, Daria; Vulf, Maria; Chasovskikh, Nataliya; Komar, Aleksandra; Kirienkova, Elena; Shunkin, Egor; Zatolokin, Pavel; Litvinova, Larisa (Frontiers in Genetics, 2021)
Type 2 diabetes mellitus (T2DM) is one of the most prominent and socially significant problems. The present study aimed to identify the mechanisms of interaction of critical regulators of carbohydrate metabolism using bioinformatics and experimental methods and to assess their influence on the development of T2DM. We conducted an in silico search for the relationship of hormones and adipokines and performed functional annotation of the receptors for ghrelin and incretins. Hormones and adipokines were assessed in the plasma of obese patients with and without T2DM as well as after laparoscopic sleeve gastrectomy (LSG) and Roux-en-Y gastric bypass (RYGB) surgeries. Incretin- and ghrelin-associated functions and metabolic processes were discovered. Low ghrelin levels were observed in obese patients without T2DM compared with healthy volunteers and the other groups. The highest ghrelin levels were observed in obese patients with T2DM. This defence mechanism against insulin resistance could be realized through the receptors: G-protein-coupled receptor (GPCR), Growth hormone secretagogue receptor (GHSR), and growth hormone-releasing hormone receptor (GHRHR). These receptors are associated with proliferative, inflammatory, and neurohumoral signalling pathways and regulate responses to nutrient intake. Signalling through the GPCR class unites ghrelin, glucagon, glucose‐dependent insulinotropic polypepide (GIP) and glucagon‐like peptide (GLP)‐1. The ghrelin impairs carbohydrate and lipid metabolism in obese patients. Ghrelin is associated with elevated plasma levels of insulin, glucagon, and leptin. Specific activation of receptors and modulation by posttranslational modifications of ghrelin can control IR's development in obesity, which is a promising area for research.